Prevalence and associated factors of diabetes mellitus among patients with tuberculosis in South Korea from 2011 to 2018: a nationwide cohort study. Issue 3 (8th March 2023) - Jeong, Dawoon; Mok, Jeongha; Jeon, Doosoo; Kang, Hee-Yeon; Kim, Hee Jin; Kim, Hee-Sun; Seo, Jeong Mi; Choi, Hongjo; Kang, Young Ae
Abstract : Objectives: This study aimed to identify the prevalence of diabetes mellitus (DM) among patients with tuberculosis (TB) using a nationwide cohort in South Korea. Design: A retrospective cohort study. Setting: This study used the Korean Tuberculosis and Post-Tuberculosis cohort, which was constructed by linking the Korean National Tuberculosis Surveillance, National Health Information Database (NHID) and Statistics Korea data for the causes of death. Participants: During the study period, all notified patients with TB with at least one claim in the NHID were included. Exclusion criteria were age less than 20 years, drug resistance, initiation of TB treatment before the study period and missing values in covariates. Outcome measures: DM was defined as having at least two claims of the International Classification of Diseases (ICD) code for DM or at least one claim of the ICD code for DM and prescription of any antidiabetic drugs. Newly diagnosed DM (nDM) and previously diagnosed DM (pDM) were defined as DM diagnosed after and before TB diagnosis, respectively. Results: A total of 26.8% (70 119) of patients were diagnosed with DM. The age-standardised prevalence increased as age increased or income decreased. Patients with DM were more likely to be men, older, had the lowest income group, had more acid-fast bacilli smear and culture positivity, had a higher Charlson Comorbidity Index score and had more comorbidities compared with patients without DM. Approximately 12.5% (8823) patients had nDM and 87.4% (61 296) had pDM among those with TB-DM. Conclusions: The prevalence of DM among patients with TB was considerably high in Korea. To achieve the goal of TB control and improve the health outcomes of both TB and DM, integrated screening of TB and DM and care delivery in clinical practice are necessary.